Evaluating an Environment-Based Learning Model Oriented Towards ESD to Foster Environmental Care Character in Madrasah Ibtidaiyah Students - Mukaromah, Ning; Suadi, Suadi; Maso, Wafaa (Bidayatuna Jurnal Pendidikan Guru Mandrasah Ibtidaiyah, 2025)
Environmental education is pivotal in shaping sustainable character among students, particularly within ecologically vulnerable regions. This study investigates the implementation of an environment-based learning model structured through the 4D framework—Discover, Deepen, Develop, and Demonstrate—to foster environmental care character among students at a coastal Islamic elementary school in Pasuruan, Indonesia. Employing a qualitative case study design, data were collected through semi-structured interviews, classroom observations, document analysis, and a supporting questionnaire involving three teachers, one curriculum coordinator, and thirty Grade 5 students. Data analysis was conducted manually using Miles and Huberman’s interactive model, enabling in-depth thematic exploration aligned with the 4D learning stages. The findings demonstrate that the sequential application of the 4D model significantly enhanced students’ environmental awareness, moral reflection, responsibility, and action orientation. Contextual, hands-on activities such as tree planting, waste management projects, and thematic discussions anchored in Islamic ethical values contributed to the profound internalization of sustainability principles. Pedagogical alignment between planning, implementation, and assessment further reinforced the model’s transformative impact. This study concludes that environment-based learning through a structured 4D framework offers an effective pathway for character development in Islamic education and provides practical insights for curriculum innovation in ecologically sensitive educational settings.